The Effect of Liquidity and Total Asset Turnover on Profitability: Research Study n Pharmaceutical Companies in Indonesia Stock Exchange - Jocelyn Rajagukguk; Harlyn Siagian (Ekonomis: Journal of Economics and Business, 2021)
Management companies will seize opportunities in order to improve financial performance. To measure the financial performance it will need the tool to measure it. Profitability ratio is a ratio to assess the company's ability to seek profit. And in this research it stated that liquidity and total asset turnover can affected profitability. The population of this study uses data from pharmaceutical companies listed on the Indonesia Stock Exchange in 2015-2019. So, it has 9 companies according to the given category. In total there are 45 samples used in this research. The result of this research are that liquidity has a negative effect on profitability, and so the total assets turnover on profitability. Simultaneously, liquidity and total asset turnover have a significant negative relationship to profitability.